Analysis of the Music of Prestij Meselesi in the Context of Adorno’s Critical Sociology of Music - İbrahim Öksüz (Filmvisio)
In his article titled “Introduction to the Sociology of Music,” Theodor W. Adorno discusses critical music sociology, which involves gathering information about the social structures that leave an imprint on music and what is generally referred to as the music life. In the age of modern consciousness and unconscious industries, the main focus of music sociology is on the forces of production and the relations of production. Another aspect of production relations is the mindset and tastes of the listeners. Adorno makes a distinction between ‘light’ and ‘serious’ music in his sociology of music. Serious music is that which aligns with the essence of art and contributes to the individual and social consciousness of its listeners. Light music,on the other hand, considers the demands of the capitalist social structure and conceals existing economic relations and class inequalities. As a product of the Culture Industry, it is designed in the form of mass-produced music for mass consumption. This study analyzes the function of the light music Adorno mentioned in mainstream cinema and the visual and auditory codes it employs, using the 2023 film Prestij Meselesi as a case study. The music used in Prestij Meselesi and the reflections of the arabesque/fantasy music products, which form the subject of the film, in social life are examined from a critical music sociology perspective.The study includes the views of various Western and Eastern thinkers who have presented opinions on music and the sociology of music. The views of Plato, Aristotle, Ibn Khaldun, Al-Farabi, Al-Kindi, Georg Simmel, and Max Weber on music are presented. Adorno’s critical music sociology is elaborated upon, and the film Prestij Meselesi chosen as a sample for the study is analyzed.